Pengaruh Kemampuan Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai pada Dinas Koperasi, UKM dan Tenaga Kerja Kota Blitar di Era Society 5.0 - Salsabila, Diva Sintana; Damayanti, Kristya (Universitas Nusantara PGRI Kediri, 2024)
Globalization drives the integration of the world economy through the rapid advancement of science and technology, creating a dynamic situation that affects digital-based industries. Technology is now used in almost all fields, including business operations. The purpose of researchers conducting this study is to determine the effect of work ability and work environment on employees of the Blitar City Cooperative, SME, and Labor Office. Most employees are between 41-60 years old, which indicates a challenge in terms of technical knowledge. This study uses a quantitative method with data collection through a questionnaire using a likert scale. The data was then analyzed using multiple linear regression with SPSS version 19. The research sample included the entire population of 42 employees. The results showed that partially work ability has a significant effect on employee performance, while the other part of the work environment has no significant effect. At the same time, work ability and work environment proved to have a significant influence on employee performance. The R-squared result of employee performance level with a percentage of 74.5% is influenced by work ability and work environment variables, and there are other factors outside the two variables with a percentage of 25.5% influenced by other variables not used in this study. This study shows that the improvement of work ability and work environment